Caracterização dos aglomerados abertos NGC1981 e Dolidze-Dzim1 - Francisco Ferreira de Souza Maia (2007)
The main goal of this work is to characterize the objects NGC1981 and Dolidze-Dzim 1 catalogued as open clusters. We have collected Johnson-Cousins BV(RI)c photometric data using the IAG 0.6m telescope at OPD/LNA on the nights 21=09=2000 and 05=08=2001.The CCD data processing method consists of standard IRAF pre-reduction techniques allied to Landolt standard stars calibration for the determination of the cluster star's magnitudes. Furthermore we have matched the elds and mapped their intersection areas by means of an IDL script which identies and excludes multi-eld incident stars basedon border distance criteria. We have applied interstellar reddening correction and isochrone tting methods to determine the physical parameters reddening, distance modulus and age for the studiedobjects. Reddening calculation was done using a linear tting to an empirical ZAMS on twocolor diagrams as proposed by Munari & Carraro (1996). We have found a color excess of E(B ..V ) = 0:100:02 for NGC1981 but we could not apply this method to Dolidze-Dzim 1 because the stars in the eld apparently do not constitute a physical system.Ages and distances were determined by isochrone tting, using the Padova grid (Z =0:019) and Siess et al. (2000) pre-main sequence grid (Z=0.020), both with overshooting. In the case of NGC1981, due to the lack of supergiant stars, the tting gives best results when the pre-main sequence tracks are considered, indicating an age between 6:7 log(t) 7:0 and true distance modulus of 8:6 0:2. The corresponding distance is 45550 ..42 pc. These values show deviations up to 15% from those published by Kharchenko et al. (2005), having our results however been determinated with a larger sample of stars. The photometric analysis done, suggests that no particular isochrone can be t onDolidze-Dzim 1 data, indicating that the presumed cluster does not constitute a physical system, being an asterism. This result is corroborated by the literature information that the stars' proper motion shows no coherence among them.